2020
DOI: 10.3390/jintelligence8010006
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Self-Estimated Intelligence

Abstract: This paper reports two studies examining correlates of self-estimated intelligence (SEI). In the first, 517 participants completed a measure of SEI as well as self-estimated emotional intelligence (SEEQ), physical attractiveness, health, and other ratings. Males rated their IQ higher (74.12 vs. 71.55) but EQ lower (68.22 vs. 71.81) than females but there were no differences in their ratings of physical health in Study 1. Correlations showed for all participants that the higher they rated their IQ, the higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Moreover, we are interested in the self-perceptions of savers and spenders. There is a growing literature which has shown simple self-ratings on things such as intelligence, health, and attractiveness are subtle markers of self-esteem with many correlates (Furnham & Grover, 2020a, 2020b; Furnham, 2021a). We assume that overall that being a saver is “psychologically healthier” than being a spender and that the former would have more positive self-ratings.…”
Section: Spenders and Spendthriftsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we are interested in the self-perceptions of savers and spenders. There is a growing literature which has shown simple self-ratings on things such as intelligence, health, and attractiveness are subtle markers of self-esteem with many correlates (Furnham & Grover, 2020a, 2020b; Furnham, 2021a). We assume that overall that being a saver is “psychologically healthier” than being a spender and that the former would have more positive self-ratings.…”
Section: Spenders and Spendthriftsmentioning
confidence: 99%
“…In this study we examine people’s comparative ratings on a wide range of factors from attractiveness to intelligence. There is an extensive literature on the relationship between self-estimates and actual behavior, particularly in the area of intelligence (Furnham & Grover, 2020b). The data suggest that correlations between self-ratings and objective or test-based measures are .25 < r < .50, suggesting people are reasonably accurate.…”
Section: Study 4: Self Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with 9th grade students from Latvia, it was found that self-efficacy in mathematics was higher for boys ( Kvedere 2014 ). Self-estimates of intelligence and test scores are low to moderately correlated in research with various samples ( Rammstedt and Rammsayer 2002 ; Furnham and Grover 2020 ). Research also shows that undergraduate students with lower performance are more likely to overestimate themselves but are aware of the possible inaccuracy, and students with higher performance are more accurate in their self-evaluation ( Miller and Geraci 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we included a simple short measure of self-evaluations. There is an extensive literature from various areas of psychology from the extensive work on Core Self-Evaluations ( Judge and Bono, 2001 ) to Self-Assessed intelligence and attractiveness ( Swami et al, 2007 ; Kornilova et al, 2009 ; Furnham and Grover, 2020 ) that suggests that positive self-evaluations are psychologically healthy with important behavioral consequences. In short, people who feel good about themselves tend to have a more benevolent and less malevolent view of others.…”
Section: Introductionmentioning
confidence: 99%